Improved salt tolerance of Chenopodium quinoa Willd. contributed by Pseudomonas sp. strain M30-35 - Cai,Deyu; Xu,Ying; Zhao,Fei; Zhang,Yan; Duan,Huirong; Guo,Xiaonong (PeerJ, 2021)
Background Plant-growth-promoting rhizobacteria (PGPR) can promote plant growth and enhance plant tolerance to salt stress. Pseudomonas sp. strain M30-35 might confer abiotic stress tolerance to its host plants. We evaluated the effects of M30-35 inoculation on the growth and metabolite accumulation of Chenopodium quinoa Willd. during salt stress growth conditions. Methods The effects of M30-35 on the growth of C. quinoa seedlings were tested under salt stress. Seedling growth parameters measured included chlorophyll content, root activity, levels of plant- phosphorus (P), and saponin content. Results M30-35 increased biomass production and root activity compared to non-inoculated plants fertilized with rhizobia and plants grown under severe salt stress conditions. The photosynthetic pigment content of chlorophyll a and b were higher in M30-35-inoculated C. quinoa seedlings under high salt stress conditions compared to non-inoculated seedlings. The stability of P content was also maintained. The content of saponin, an important secondary metabolite in C. quinoa, was increased by the inoculation of M30-35 under 300 mM NaCl conditions. Conclusion Inoculation of M30-35 rescues the growth diminution of C. quinoa seedlings under salt stress.
Keywords: Pseudomonas sp. strain M30-35; Chenopodium quinoa; Salt stress; Photosynthesis; Plant-growth-promoting